2017
DOI: 10.1002/ijc.31133
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte membrane fatty acids and breast cancer risk: a prospective analysis in the nurses' health study II

Abstract: The roles of specific fatty acids in breast cancer etiology are unclear, particularly among premenopausal women. We examined 34 individual fatty acids, measured in blood erythrocytes collected between 1996 and 1999, and breast cancer risk in a nested case-control study of primarily premenopausal women in the Nurses' Health Study II. Breast cancer cases diagnosed after blood collection and before June 2010 (n = 794) were matched to controls and conditional logistic regression was used to estimate OR's (95% CI's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 50 publications
8
44
11
1
Order By: Relevance
“…Palmitelaidic acid is a natural trans fatty acid produced by microbial hydrogenation of palmitoleic acid in the rumen of ruminants and, consequently, is present in all fats of these animals [ 54 ], although it can also be produced endogenously by the partial β oxidation of dietary vaccenic acid [ 55 ]. Although studies evaluating the relationship between BC and levels of this trans fatty acid in biomarkers are scarce, positive associations have been described in the serum of current postmenopausal smokers [ 56 ], in the erythrocytes membrane of overweight/obese women from the Nurses’ Health Study II [ 17 ], and in the plasma of a cohort of Australian women, although in the latter case the association was only found with ER-/PR- tumors [ 16 ]. Elaidic acid, the trans form of oleic acid, is the main industrial trans fatty acid that is produced during the partial hydrogenation of vegetable oils, and is a reliable biomarker of highly processed foods among European populations [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palmitelaidic acid is a natural trans fatty acid produced by microbial hydrogenation of palmitoleic acid in the rumen of ruminants and, consequently, is present in all fats of these animals [ 54 ], although it can also be produced endogenously by the partial β oxidation of dietary vaccenic acid [ 55 ]. Although studies evaluating the relationship between BC and levels of this trans fatty acid in biomarkers are scarce, positive associations have been described in the serum of current postmenopausal smokers [ 56 ], in the erythrocytes membrane of overweight/obese women from the Nurses’ Health Study II [ 17 ], and in the plasma of a cohort of Australian women, although in the latter case the association was only found with ER-/PR- tumors [ 16 ]. Elaidic acid, the trans form of oleic acid, is the main industrial trans fatty acid that is produced during the partial hydrogenation of vegetable oils, and is a reliable biomarker of highly processed foods among European populations [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the fatty acid profile in biological samples is a more accurate measure that reflects the interaction between dietary intake, de novo lipogenesis and the activity of different enzymes involved in this metabolic process [ 14 ]. Although data from a meta-analysis of prospective studies found no association between serum levels of SFAs, MUFAs and PUFAs and risk of BC [ 15 ], more recent studies have described positive associations with circulating levels of several SFAs [ 16 , 17 ], palmitoleic acid [ 18 ], some trans fatty acids [ 17 , 18 , 19 ] and the ratio of palmitoleic acid to palmitic acid (DI 16 ) [ 18 ], as well as an inverse association with n-3 PUFAs among overweight/obese women [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insights into mechanisms that may contribute to the beneficial health effects of n -3 PUFAs can be gleaned by reviewing recent work by Kiecolt-Glaser et al [106], showing that n -3 PUFAs supplementation positively impacted cell aging, thereby highlighting how inflammation, oxidative stress, and immune cell aging—which appear to be important mechanisms prior to disease onset—that may be ameliorated through nutritional interventions. Among women, n -3 PUFA intake has been found to be inversely associated with breast cancer risk [99, 100, 107, 108] and breast cancer mortality [103, 104]. Mechanisms underlying the beneficial effects of higher consumption of marine n -3 fatty acids in terms of lowering breast cancer risk might be attributed to the growth-inhibitory, pro-apoptotic, or anti-angiogenic effects of n -3 fatty acids that can be found in fish [100, 103].…”
Section: Dietary Factors and Nutrition In Breast Cancer Riskmentioning
confidence: 99%
“…Recent studies have showed that ALA reduces growth of breast cancer cell lines (MCF-7, BT-474, MDA-MB-231 and MDA-MB-468) and demonstrates a dynamic gene expression in treated breast cancer cells (Wiggins et al, 2015;Mason-Ennis et al, 2016). Hirko et al (2018) reported that there were inverse associations of n-3 PUFA (e.g. ALA) with breast cancer among overweight/obese women (BMI≥25) after examed the relationship between 34 individual fatty acids and cases.…”
Section: Ala and Cancermentioning
confidence: 99%